BUSINESS AND LABOR COALITION FOR EMPLOYEE PRIVACY (Tufts Archival Research Center, 2007)
Summarizes federal legislation that would prohibit employers from hiring or firing employees on behalf of legal activities participated in outside of the workplace. Discusses coalition agenda to support legislation.